Biomass availability for a small-scale biorefinery. A case study based on GIS - Riera, María Antonieta (2022)
On this occasion, the amount of agricultural waste was estimated, to be used as raw material in a biorefinery. The country Ecuador was taken as a case study, as it is a country with great activity of this type. A time series for annual agricultural production was constructed using the ARIMA model through RStudio software. For the main crops, the number of residues generated was estimated and after that, an analysis of vector networks was carried out through the GRASS GIS software. The results indicated that the main apparent source of waste is the banana, from which leaves, peel, rachis, and stem would be obtained, useful in the production of bioproducts. Using the GIS, it was determined that the largest number of crops are found in two regions of the country, with distances greater than 500 meters from the road network. The characteristics of Ecuador make possible the future installation of small-scale biorefineries in the country.